Análise experimental e numérica da compressibilidade de solos cimentados artificialmente - Alencar, Igor de Brito (2017)
Geotechnical projects can be conducted basically in two ways, either by adapting the structures to the soil profile or by improving the soil properties by adapting to the already defined geotechnical design. In the second case, one of the most efficient and currently very useful forms is the addition of binder to the soil generating artificial cementation. Small portions of cement provide great increases in strength and stiffness, which are very important when it is desired to have deformation limitations with more stable structures. This research had the objective of evaluating the stress-strain conditions in samples of artificially cemented soil through edometric tests with the application of different values ​​of cement contents. The result, evidently, was a non-linear behavior and with the rigidity increasing with both the increase of the compression stresses and the cement content. The research also involved the implementation of a numerical modeling in the UNSTRUCT program that uses results of oedometric tests in a sample of soil without cement and another one with maximum content of cement. The behavior for intermediate contents is calculated through a linear interpolation, in this way the modeling reduces the number of tests and allows the use of a finite element program for stress-strain prediction of cemented soils. It is worth mentioning that the experimental results show that linear interpolation presented good agreement, which justifies the use of the model proposed in this research and implemented in the UNSTRUCT program.